Historical Trauma, Ethnic Experience, and Mental Health in a Sample of Urban American Indians. (March 2020) - Guenzel, Nicholas; Struwe, Leeza
BACKGROUND: Historical trauma (HT) among American Indians (AIs) has been linked with poor mental health but has been inadequately studied among urban populations.OBJECTIVES: The purpose of this study was to describe historical trauma, historical loss associated thoughts, ethnic experience, and psychological symptoms among a population of urban AIs.METHOD: This was a mixed methods study. In addition to focus groups, survey participants were administered the Historical Losses Scale, the Historical Losses Associated Symptoms Scale, the Scale of Ethnic Experience, and the Achenbach System of Empirically Based Assessment Adult Self-Report. Rates of psychological symptoms were compared with matched controls from a normative data set.RESULTS: Participants reported a strong sense of ethnic identity, a moderate desire to associate with other AIs, moderate comfort within mainstream society, and moderately high perceived discrimination. The most common HT themes were loss of culture, respect by children of traditional ways, and language. Compared with controls, participants had higher rates of aggressive behavior, substance use, thought problems, and obsessive symptoms, but some of these issues are likely explained by cultural factors. A greater number of participants met the clinical threshold for multiple problems compared with controls.CONCLUSIONS: This sample of AIs reported frequent experiences of discrimination. HT is a significant factor in the lives of many urban AIs who also have significantly higher rates of a number of mental health problems. Providers must be aware of these issues to provide the most effective care to AIs.